Memperkenalkan Algoritma dan Berpikir Algoritmik kepada Siswa Sekolah Dasar Menggunakan CS Unplugged - Sondakh, Debby Erce; Pungus, Stenly Richard; Maringka, Raissa C; Tangka, George M. W (Universitas Klabat, 2024)
A community service was conducted aiming at introducing the concept of algorithms and algorithmic thinking to elementary school students, using the Computer Science Unplugged approach. Two main activities,